SH003 and Docetaxel Show Synergistic Anticancer Effects by Inhibiting EGFR Activation in Triple-Negative Breast Cancer. (5th May 2022) - Choi, Yu-Jeong; Lee, Kangwook; Yoon, Ji-Hye; Cho, Sung-Gook; Kim, Yun-Gyeong; Jeong, Miso; Hwang, Hyun-Ha; Lee, Seo Yeon; Jung, Se-Eun; Ko, Seong-Gyu
Abstract : Although many anticancer drugs have been developed for triple-negative breast cancer (TNBC) treatment, there are no obvious therapies. Moreover, the combination of epidermal growth factor receptor- (EGFR-) targeted therapeutics and classical chemotherapeutic drugs has been assessed in clinical trials for TNBC treatment, but those are not yet approved. Our serial studies for newly developed herbal medicine named SH003 provide evidence of its broad effectiveness in various cancers, especially on TNBC. The current study demonstrates a synergic effect of combinatorial treatment of SH003 and docetaxel (DTX) by targeting EGFR activation. The combinatorial treatment reduced the viability of both BT-20 and MDA-MB-231 TNBC cells, displaying the synergism. The combination of SH003 and DTX also caused the synergistic effect on apoptosis. Mechanistically, the cotreatment of SH003 and DTX inhibited phosphorylation of EGFR and AKT in both BT-20 and MDA-MB-231 cells. Moreover, our xenograft mouse tumor growth assays showed the inhibitory effect of the combinatorial treatment with no effect on body weight. Our immunohistochemistry confirmed its inhibition of EGFR phosphorylation in vivo. Collectively, combinatorial treatment of SH003 and DTX has a synergistic anticancer effect at a relatively low concentration by targeting EGFR in TNBC, indicating safety and efficacy of SH003 as adjuvant combination therapy with docetaxel. Thus, it is worth testing the combinatorial effect in clinics for treating TNBC.